2012
DOI: 10.1364/oe.20.008551
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved imaging of near-fields in THz antennas and direct quantitative measurement of field enhancements

Abstract: We investigate the interaction between terahertz waves and resonant antennas with sub-cycle temporal and λ/100 spatial resolution. Depositing antennas on a LiNbO₃ waveguide enables non-invasive electro-optic imaging, quantitative field characterization, and direct measurement of field enhancement (up to 40-fold). The spectral response is determined over a bandwidth spanning from DC across multiple resonances, and distinct behavior is observed in the near- and far-field. The scaling of enhancement and resonant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…The spatial selectivity was achieved by attaching the sample under test to a metallic screen with a sub-wavelength aperture (as small as 10 lm) 15 or by placing the sample on an electro-optic crystal directly. 16,17 The spatial resolution in the latter case is of the order of several tens of lm, determined by the electro-optics crystal thickness. 16,17 Here we investigate the interaction of Z-TSWs with sub-wavelength size dielectric particles placed between a THz planar antenna and a metallic plane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial selectivity was achieved by attaching the sample under test to a metallic screen with a sub-wavelength aperture (as small as 10 lm) 15 or by placing the sample on an electro-optic crystal directly. 16,17 The spatial resolution in the latter case is of the order of several tens of lm, determined by the electro-optics crystal thickness. 16,17 Here we investigate the interaction of Z-TSWs with sub-wavelength size dielectric particles placed between a THz planar antenna and a metallic plane.…”
mentioning
confidence: 99%
“…16,17 The spatial resolution in the latter case is of the order of several tens of lm, determined by the electro-optics crystal thickness. 16,17 Here we investigate the interaction of Z-TSWs with sub-wavelength size dielectric particles placed between a THz planar antenna and a metallic plane. We demonstrate that near-field mapping of the surface field enables direct detection of the particles.…”
mentioning
confidence: 99%
“…To study the effects in the strong-field limit, the strength of the terahertz field can be locally enhanced exploiting near-field effects in meta-materials [3,[15][16][17][18][19][20], which typically consist of micrometer-sized metallic structures deposited on the sample surface. However, since the area of the sample is often significantly smaller than the area of metallic structures in meta-materials, the reflectivity in the visible or near-infrared frequency range of the probe is dominated by the latter.…”
Section: Introductionmentioning
confidence: 99%
“…The relation between the near-field response of a structure and its far-field spectrum has been the subject of several studies that have consistently reported a small yet distinct shift between the near-and far-field resonant frequencies [16][17][18][19][20]. The origin of this shift is ascribed to the intrinsic damping of the structure and has been modeled using the damped-driven oscillator model [19].…”
Section: Introductionmentioning
confidence: 99%